Georgia : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Georgia. (IMF Staff Country Reports; Country Report, 2021)
High frequency estimates suggest a V-shaped recovery with output now poised to return close to 2019 levels already this year, much earlier than expected. Recently COVID-19 case numbers have risen sharply to new highs while vaccinations have also accelerated significantly after a slow start. The recovery has improved the fiscal outlook and the authorities submitted to Parliament a supplementary budget, with GEL 1.2 billion in additional spending roughly equivalent to the expected increase in revenues. The National Bank of Georgia (NBG) has increased the policy rate by 200 basis points to deal with high inflation driven by lagging effects of depreciation, commodity and food price increases, and supply side constraints.